Status of Scar in Repeat Cesarean Section in a Tertiary Hospital - Shrestha, Subha; Shakya, Raju; Shrestha, Buddhi Kumar; Kaur, Narinder; Thapa, Babita (Journal of Lumbini Medical College, 2017)
Introduction: In modern Obstetrics, with rising trends of primary cesarean section (CS) for fetal and maternal interests, pregnancy over the scarred uterus is a challenge to all treating obstetricians. Despite the method of suturing of the cesarean scar, its fate in next pregnancy is still not measurable. Objective of this study was to evaluate the status of previous cesarean scar during repeat cesarean section (RCS) and calculate the maternal morbidity in those cases in a tertiary hospital. Methods: It was a descriptive, retrospective study conducted at department of Obstetrics of Lumbini Medical College Teaching Hospital. The study was conducted from 15th July 2014 to 14thJuly 2015. The data were retrieved from the department of Medical Records. Women undergoing RCS were enrolled. The status of scar was evaluated in terms of intact scar, scar rupture, scar dehiscence, thin lower uterine segment, scar placenta previa, and adhesions as indicator of scar integrity. Results: There were 534 (25.4%) CS among 2,098 deliveries during the study period. Ninety one (17.04%) of them were RCS. Elective RCS were 73.6% (n=67), and emergency RCS were 26.4% (n=24). Eighty two (90.1%) women had RCS once and nine (9.9%) had RCS for second time. Scar was intact in 22 (91.6%), scar dehiscence in one (8.3%), scar with adhesions in one (8.3%) among emergency RCS and intact in 53 (91.3%) and scar with adhesions in five (8.7%) among elective RCS. There was no scar dehiscence and no scar rupture in two RCS women. Adhesions were documented twice higher in women whose primary CS was undertaken outside our hospital. Placenta previa and placenta accreta each were found in two cases. Conclusion: Most of the scars of repeat cesarean section were healthy with no scar rupture. We can consider trial of labor for scarred uterus with strict vigilance and in need, CS is always an option. DOI: https://doi.org/10.22502/jlmc.v4i1.84 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, page: 42-45